Pengaruh Psychological Capital dan Perceived Organisational Support terhadap Teacher Burnout dengan Job Satisfaction sebagai Variabel Mediator di SMK T Surabaya - Muhammad Faiz Fairuz; Cholichul Hadi (Departement of Mathematics Education, 2023)
Teacher burnout is a negative syndrome that could happen to teachers that will affect their performance, hence, lowers their students’ achievements. The goal of this paper was to confirm the direct effect of psychological capital and perceived organizational support towards teacher burnout, and the indirect effect of psychological capital and perceived organizational support towards teacher burnout with job satisfaction as a mediating variable.This research used quantitative approach with census as the sampling method. The data collection instrument used was a likert scale questionnaire in Bahasa Indonesia to measure every single variable in this research. Subjects of this research were 58 teachers of Sejahtera Vocational School in Surabaya. This research used path analysis to prove the direct and indirect effects of psycap and POS on teacher burnout with job satisfaction as the mediating variable. This paper showed that psychological capital and perceived organizational support directly affect teacher burnout significantly, and psychological capital and perceived organizational support indirectly affect teacher burnout through job satisfaction as a mediating variable significantly.